2009
DOI: 10.1136/thx.2008.111492
|View full text |Cite
|
Sign up to set email alerts
|

Short-term comparative study of high frequency chest wall oscillation and European airway clearance techniques in patients with cystic fibrosis

Abstract: BackgroundHigh frequency chest wall oscillation (HFCWO) is standard treatment for airway clearance in the USA and has recently been introduced in the UK and Europe. There is little published research comparing HFCWO with airway clearance techniques (ACTs) frequently used in the UK and Europe. The aim of this study was to compare the short-term effects of HFCWO with usual ACTs in patients with cystic fibrosis hospitalised with an infective pulmonary exacerbation.MethodsA 4-day randomised crossover design was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 22 publications
1
74
0
3
Order By: Relevance
“…As for spirometry, our findings are consistent with previous studies in which they noted improvement in spirometric values after airway clearance techniques 18,24,25 . Similarly to our study, Bellone et al 8 did not find significant differences in FEV 1 between Flutter ® and ELTGOL in patients with acute exacerbation of chronic bronchitis.…”
Section: Discussionsupporting
confidence: 83%
“…As for spirometry, our findings are consistent with previous studies in which they noted improvement in spirometric values after airway clearance techniques 18,24,25 . Similarly to our study, Bellone et al 8 did not find significant differences in FEV 1 between Flutter ® and ELTGOL in patients with acute exacerbation of chronic bronchitis.…”
Section: Discussionsupporting
confidence: 83%
“…high-frequency chest wall oscillation, non-invasive ventilation) being reserved for sicker patients. However, recent trials comparing high-frequency chest wall oscillation with PEP have raised uncertainty regarding the effectiveness of high-frequency chest wall oscillation for airway clearance [13,32]. It will be interesting to repeat a similar analysis in several years' time to determine if the pattern of airway clearance techniques changes with emerging evidence.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…For example, in a qualitative study 16 of thoracic surgery patients, 84% of the patients had little or no discomfort with HFCWO, as compared with conventional CPT. Osman and colleagues 15 found no significant differences between HFCWO and the usual airway clearance method with respect to scores for comfort measured on a visual analog scale. 15 Conversely, Oermann et al 2 reported that the Flutter, a portable device that provides positive expiratory pressure, 22 was better tolerated and more comfortable than HFCWO and postural drainage, percussion, and vibration.…”
Section: Figurementioning
confidence: 99%
“…Osman and colleagues 15 found no significant differences between HFCWO and the usual airway clearance method with respect to scores for comfort measured on a visual analog scale. 15 Conversely, Oermann et al 2 reported that the Flutter, a portable device that provides positive expiratory pressure, 22 was better tolerated and more comfortable than HFCWO and postural drainage, percussion, and vibration. One possible explanation for our results may be that the vest is clothlike and covers the entire thorax and the upper part of the abdomen, whereas CPT involves striking over the chest wall with rubber percussors.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation